The somatic mutation profiles of 2,433 breast cancers refine their genomic and transcriptomic landscapes - Bernard Pereira (Nature Portfolio, 2016)
Much effort has recently been devoted to understanding the genomics of breast cancer. In this study, the authors integrate somatic mutation data with previously published copy number aberration and gene expression information for nearly 2,500 breast cancer samples.